2003
DOI: 10.1002/mma.446
|View full text |Cite
|
Sign up to set email alerts
|

Solution representations for a wave equation with weak dissipation

Abstract: SUMMARYWe consider the Cauchy problem for the weakly dissipative wave equationparameterized by ¿0, and prove a representation theorem for its solutions using the theory of special functions. This representation is used to obtain Lp-Lq estimates for the solution and for the energy operator corresponding to this Cauchy problem.Especially for the L 2 energy estimate we determine the part of the phase space which is responsible for the decay rate. It will be shown that the situation depends strongly on the value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 14 publications
6
120
0
Order By: Relevance
“…To prove them we follow the approach used in [25] to derive L 2 − L 2 estimates for the linear damped wave equation…”
Section: Linear Estimatesmentioning
confidence: 99%
“…To prove them we follow the approach used in [25] to derive L 2 − L 2 estimates for the linear damped wave equation…”
Section: Linear Estimatesmentioning
confidence: 99%
“…The damping term of this model is not effective (see [27]). Nevertheless, there should be an improving influence on the critical exponent p crit in comparison with Strauss exponent p 0 (n) for      w tt − △w = |w| p , t ≥ 0, x ∈ R n , w(0, x) = w 0 (x), x ∈ R n , w t (0, x) = w 1 (x), x ∈ R n ,…”
Section: Introductionmentioning
confidence: 98%
“…It has been recently shown that the critical exponent for models with effective dissipation, this means, µ is sufficiently large (see [27])…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, if β > 1 then the asymptotic profile of the solution of (1.2) is given by that of the free wave equation w = 0 (see [13]). Wirth [12] considered the linear problem…”
Section: Introductionmentioning
confidence: 99%